2022
DOI: 10.1186/s12889-022-13217-6
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the consumption trend of proton pump inhibitors in the Lleida Health Region between 2002 and 2015

Abstract: Background Proton pump inhibitors (PPIs) are one of the most commonly prescribed pharmacological groups. Their high prevalence and duration of use are of important health concern due to the risk they can cause to patients. Despite these risks, their use remains particularly high, especially in the elderly population. We determined the trend in the prevalence of PPI consumption in the population of the Lleida Health Region between 2002 and 2015 to explore patterns of use and associated character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 33 publications
2
24
1
Order By: Relevance
“…Similarly, by cumulative effect, the number of prevalent chronic drug users increased very slightly from 4.2% in 2017 to 4.4% in 2020 (p < 0.0001). Even though the sharp increase of the absolute number of incident chronic consumers in 2020 has no explanation to this day, this overall increasing trend in PPIs consumption is comparable to that observed in other European countries such as the United Kingdom or Spain, and confirms the global overconsumption of PPIs [23,24].…”
Section: Discussionsupporting
confidence: 60%
“…Similarly, by cumulative effect, the number of prevalent chronic drug users increased very slightly from 4.2% in 2017 to 4.4% in 2020 (p < 0.0001). Even though the sharp increase of the absolute number of incident chronic consumers in 2020 has no explanation to this day, this overall increasing trend in PPIs consumption is comparable to that observed in other European countries such as the United Kingdom or Spain, and confirms the global overconsumption of PPIs [23,24].…”
Section: Discussionsupporting
confidence: 60%
“…In recent years, there have been concerns about the increased prevalence of PPI use 12. Despite the increased prevalence of PPI use in previous studies,2 5 6 13 28 findings of this study show a decrease in the rate of PPI prescriptions, PPI use and expenditure.…”
Section: Discussioncontrasting
confidence: 68%
“…Similarly, in Denmark, the prevalence of PPI use increased by fourfold between 2002 and 2013, reaching 7.4% in 2014 10. Moreover, in Spain, the annual prevalence of PPI showed an upward trend from 11.3% (2002) to 18.0% (2015) 13. In addition, in Australia, the prevalence of PPI use was 12.6% in 2016 14.…”
Section: Introductionmentioning
confidence: 93%
“…A recent cohort study found that antibodies of AIG were associated with increased gastric cancer risk, being strongest in non-cardia locations [ 30 ]. There was also speculation of more antibiotics and proton-pump inhibitor (PPI) therapy use in women than men [ 31 ], which alter the gut microbiome potentially eliciting an inflammatory response. Altogether, the higher risk for autoimmunity and medication-induced inflammatory states in young women than men may play a role in the sex-specific differences in primary NCGC incidence seen in this study.…”
Section: Discussionmentioning
confidence: 99%